CHANG-ES XXIX: the sub-kpc nuclear bubble of NGC 4438. Issue 2 (2nd August 2022) - Li, Jiang-Tao; Wang, Q Daniel; Wiegert, Theresa; Bregman, Joel N; Beck, Rainer; Damas-Segovia, Ancor; Irwin, Judith A; Ji, Li; Stein, Yelena; Sun, Wei; Yang, Yang
ABSTRACT: Active galactic nucleus (AGN) bubbles could play an important role in accelerating high-energy cosmic rays (CRs) and galactic feedback. Only in nearby galaxies could we have high enough angular resolution in multiwavelengths to study the sub-kpc environment of the AGN, where the bubbles are produced and strongly interact with the surrounding interstellar medium. In this paper, we present the latest Chandra observations of the Virgo cluster galaxy NGC 4438, which hosts multiscale bubbles detected in various bands. The galaxy also has low current star formation activity, so these bubbles are evidently produced by the AGN rather than a starburst. We present spatially resolved spectral analysis of the Chandra data of the ∼3 arcsec × 5 arcsec (${\sim} 200{\rm ~pc}× 350\rm ~pc$ ) nuclear bubble of NGC 4438. The power-law tail in the X-ray spectra can be most naturally explained as synchrotron emission from high-energy CR leptons. The hot gas temperature increases, while the overall contribution of the non-thermal X-ray emission decreases with the vertical distance from the galactic plane. We calculate the synchrotron cooling time-scale of the CR leptons responsible for the non-thermal hard X-ray emission to be only a few tens to a few hundreds of years. The thermal pressure of the hot gas is about three times the magnetic pressure, but the current data cannot rule out the possibility that they are still in pressure balance. The spatially resolved spectroscopy presented in this paper may have important constraints on how the AGN accelerates CRs and drives outflows. We also discover a transient X-ray source only ∼5 arcsec from the nucleus of NGC 4438. The source was not detected in 2002 and 2008, but became quite X-ray bright in 2020 March, with an average 0.5–7 keV luminosity of ${\sim} 10^{39}\rm ~erg~s^{-1}$ .